Income inequality and carbon emissions - Nicole Grunewald; Stephan Klasen; Inmaculada Martínez-Zarzoso; Chris Muris (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
We document a U-shaped relationship between income inequality and carbon dioxide emissions per capita, using a newly available panel data set on income inequality (GINI) with observations for 138 countries over the period 19602008. Our findings suggest that, for high-income countries with high income inequality, pro-poor growth and reduced per capita emissions levels go hand in hand.
Keywords: I3; O1; Q3; 330; environmental quality; income inequality; panel data